Una prueba de la técnica multi-espécimen para determinar paleointensidad utilizando material arqueomagnetico: resultados preliminares con arcillas quemadas Tunecinas - DEL VIGO, Angel; MCINTOSH, Gregg (Física de la Tierra, 2010)
The multispecimen palaeointensity technique of Dekkers & Böhnel (2006) has been tested on archaeomagnetic material from five kilns from Tunisia. In a previous study all five kilns yielded good quality archaeointensities based on Thellier-type double heating experiments. Results obtained using the multispecimen technique compared well with the previously studied Thellier-type results, with a slight tendency towards lower values. Markedly lower values were observed in two kilns, results that were improved by increasing the proportion of the natural remanence remagnetised in the partial thermoremanence acquisition. One of the kilns showed a multicomponent remanence (due to partial heating) and gave relatively poor results.